Türkiye’de Sinema Salonlarının Dijital Dönüşümü - Erkılıç, Hakan (The Turkish Online Journal of Design Art and Communication, 2012)
Cinema industry is changing from celluloid-based film (35mm film) production, distribution and release net to the digital production, distribution and release net. Today digital process about production phase has been completed, providing the standardization is waited. So In digital cinema distribution and release phase which seem a real problem involves suspense out of a few practice. It is underlined that right away cinema industry need to invest in digital cinema which reduces the costs to compete with innovations such as HD TV broadcasting, developing DVD market. Also, new digital technology enables film distribution, download and viewing via internet so this appeals to the audience and causes lose of audience in the movie theatres. It is asserted that with digital cinema distribution and release, costs will be lower and its positive results in the ticket prices (lower ticket price) will appeal the audience to the movie theatres again. At this point in spite of the finance ,suspense of technological standardization and inadequacy of craft, main concern is how to transform movie theatres to the digital cinema. This notice focuses on observed release aspect of digital process in Turkey cinema both in production and release field. Within this scope the question of has Turkey got a ‘policy of digital cinema’ will be answered.
Keywords: Digital Cinema; Digitization of Cinemas; Policy of Digital Cinema; Dijital Sinema; Sinemaların Sayısallaştırılması; Dijital Sinema Politikası